It’s a new day – is it? Testing accumulation and sensitisation effects of workload on fatigue in daily diary studies - Anita C. Keller; Meier, Laurenz Linus (My University, 2023)
Studies investigating the stressor–strain relation using daily diary designs have been interested in within-person deviations that predict well-being outcomes on the same day. These models typically have not accounted for the possibility of short-term accumulation (i.e. previous stressor experiences having a lasting effect and affecting strain on subsequent occasions) and sensitisation (i.e. previous stressor experiences amplifying subsequent reactions to stressors) effects of stressors such as workload across days. In this study, we test immediate, accumulation, and sensitisation effects of workload on fatigue within and across days using four diary studies (mean observations = 1,406; mean N = 166). In all four studies, we observed that workload had positive concurrent effects on fatigue. In addition, we found that workload had positive effects on fatigue within one day. However, there was insufficient support for short-term accumulation or sensitisation effects, implying that higher levels of workload on previous days did not directly affect or amplify the effect of workload on fatigue on that day. We discuss implications for recovery theories and potential future avenues to refine the theoretical propositions that describe intra-individual stress and recovery processes across days.
Keywords: Workload; fatigue; accumulation effect; sensitisation effect; daily diary studies